2015
DOI: 10.1556/1886.2015.00039
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of Toxoplasma gondii infection in female sex workers: A case-control study

Abstract: Through an age- and sex-matched case-control study, we sought to determine whether female sex workers have an increased risk of Toxoplasma gondii exposure and to determine the sociodemographic, work, clinical, and behavioral characteristics of these workers associated with T. gondii exposure. Female workers (n = 136) and controls (n = 272) were examined with enzyme-linked immunoassays (EIA) for the presence of anti-Toxoplasma IgG and IgM antibodies. IgM positive sera were additionally tested with enzyme linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
4
15
0
2
Order By: Relevance
“…In the present study, apparently healthy individuals were enrolled and T. gondii -infected subjects were likely immunocompetent and perhaps no parasite dissemination to genital organs occurred. In a recent age- and gender-matched case-control study, a high rate of T. gondii infection was found in female sex workers [ 13 ]. It is possible that a higher frequency of sexual contacts and diversity of partners in female sex workers than those in women of the present study might account for an increase in the likelihood for a T. gondii sexual transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, apparently healthy individuals were enrolled and T. gondii -infected subjects were likely immunocompetent and perhaps no parasite dissemination to genital organs occurred. In a recent age- and gender-matched case-control study, a high rate of T. gondii infection was found in female sex workers [ 13 ]. It is possible that a higher frequency of sexual contacts and diversity of partners in female sex workers than those in women of the present study might account for an increase in the likelihood for a T. gondii sexual transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of psychiatric patients, sexual promiscuity was shown to be associated with T. gondii infection [ 12 ]. In addition, a high seroprevalence of T. gondii infection was found in female sex workers in an age- and gender-matched case-control study [ 13 ]. In a recent study, Singh et al found a significantly higher prevalence of toxoplasmosis in married women than in unmarried women [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate analysis showed that T. gondii exposure was positively associated with being born in Durango State. This result was unexpected since T. gondii exposure has been repeatedly associated with the characteristic of being born out of Durango State in diverse cohorts including the general population in Durango City [20], inmates [16], patients with vision and hearing impairments, cancer, HIV, or undergoing hemodialysis [21], female sex workers [22], elderly people [23], patients with heart diseases [24], and people applying for medical certificates [25]. The association of T. gondii infection with being born in Durango State found in this study likely indicates that infection was acquired in Durango State.…”
Section: Discussionmentioning
confidence: 99%
“…2), Menschen mit Katzen oder Konsum von rohem Fleisch sind betroffener als solche ohne, Leute die auf dem Lande leben (1), oder eine geringe Bildung aufweisen, sind betroffener als Städter oder Gebildete (19). Erhöhte Infektionsraten wurden ferner bei Gefängnisinsassen (3), Prostituierten 1 (6), Müllsammlern (4) und Lastwagenfahrern (5) gefunden.…”
Section: Toxoplasmen Gehören Zu Den Weltweit Am Meisten Verbreiteten unclassified
“…Damit wird immer unwahrscheinlicher, dass Toxoplasmen lediglich unspezifische Symptome einer leicht verlaufenden Encephalitis (wenn überhaupt) hervorrufen und 6; p = 0,008). Infektionen mit Cytomegalie (CMV) und Herpes-simplex-Virus-Typ-1 (HSV-1) hatten keinen entsprechenden Effekt.…”
Section: Dass Toxoplasmen Bei Manchenunclassified